Phosphorus dynamics in soils amended with alternative sources of phosphate fertilizers - Sousa, Rodrigo Nogueira de (2024)
The need for phosphate fertilization in tropical soils is underscored by Brazil\'s significant agricultural production and high dependence on fertilizer imports. About 85% of agricultural fertilizers, including phosphates, are imported, there is an urgent need to explore alternative fertilizer sources. These alternatives are crucial to improve phosphorus use in agriculture, especially in tropical soils where phosphate availability is often limited, addressing both economic and environmental sustainability concerns. The dynamics of phosphorus (P) have captivated researchers worldwide since its recognition as an essential element for life. This element has high reactivity in soils and is often a limiting factor for agricultural production in humid tropical regions. Overall, this thesis integrates multidisciplinary approaches to understand the chemical, physical, and biological aspects of soil in response to alternative phosphate fertilizers. The thesis begins in Chapter 2 with a study of the accuracy of extractors for available P contents (resin, Mehlich-1, and Mehlich-3) in tropical soils grown with maize (Zea mays) and fertilized with mineral and alternative P sources. The resin method had the best correlation with plant P uptake, demonstrating its effectiveness in highly weathered soils, while Mehlich-1 and Mehlich-3 methods tended to overestimate P values. In chapter 3, the performances of struvite (Est), organomineral (OM), thermophosphate (ThermoP), and triple superphosphate (TSP) fertilizers in maize yield were evaluated by means of agronomic efficiency indices. Est and OM outperformed TSP in the sandy-loamy soil, with almost twice the efficiency compared to a clayey soil. The gradual release of nutrients from these alternative sources resulted in better P utilization by plants. The effects of mineral and alternative P fertilizers on soil microbiota and maize biomass were explored in chapter 4. Est and OM fertilizers not only improved soil P status but also enriched microbial communities and increased maize biomass. OM fertilizer enhanced P fractions and microbial diversity, while Est promoted the proliferation of P-solubilizing bacteria, including beneficial genera. Finally, the miscible displacement of P in tropical soils, considering soil pH, texture, and P sources were evaluated in chapter 5. A column experiment was used to simulate the movement of P in soil profiles under varying pH conditions. Adjustments in soil pH affected P dynamics, emphasizing the importance of balanced fertilization strategies to optimize P availability and minimize leaching risk, especially in sandy soils. Taken together, these chapters provide a comprehensive view of the efficacy of alternative P fertilizer sources in humid tropical soils and highlight their positive impact on nutrient availability, environmental, soil health, and agricultural productivity.